A granitic inclusion suite within igneous zircons from a 3.81 Ga tonalite (W.Greenland): Restrictions for Hadean crustal evolution studies using detrital zircons - Nutman, Allen P; Hiess, Joe (Research Online, 2009)
This paper presents an electron microprobe study of inclusions within igneous zircons from ca. 3800 Ma metatonalite sample G97/18. Crystalline inclusions are K-feldspar. plagioclase, quartz, hornblende, biotite, ilmenite and apatite. Additionally, one globular polymineralic inclusion interpreted as crystallised melt occurs at the surface of a polished grain mount. This consists of plagioclase + quartz + K-feldspar around a biotite lath. Other similar, but rare globular inclusions were seen buried within other zircons below the polished surface. These inclusions, particularly the presence of K-feldspar and plagioclase in broadly equal amounts, entail crystallisation of the zircons from a (residual) granitic (sensu-stricto) melt rather than a tonalitic melt. SHRIMP (Sensitive High Resolution Ion MicroProbe) U/Pb dating of zircons with inclusions indicates that they grew at ca. 3800 Ma (the accepted igneous age of the rock). This inclusion suite is compatible with the low Ti-in-zircon temperatures for G97/18 igneous zircon ( Hiess et al., 2008). Therefore, low Ti-in-zircon temperatures and "granitic" inclusions found in Hadean detrital zircons do not necessitate crystallisation from low temperature granites, because such features would also be found if Hadean zircons had crystallised (late) from higher temperature zircon-undersaturated melts of tonalitic composition. (C) 2008 Elsevier B.V. All rights reserved.